Legal assistance for improving waqf management: Nazhir replacement within Muhammadiyah in Malang Regency - Luthfi, Muhammad; Hapsari, Dwi Ratna Indri (Community Empowerment, 2025)
This community service activity aimed to facilitate improved waqf management through legal assistance related to the process of replacing waqf administrators (nazhir) and fulfilling document completeness within the Muhammadiyah organization in Malang Regency. Implemented through classical and individual approaches, the program successfully enhanced partners' understanding and knowledge of nazhir replacement regulations, as evidenced by pre-test and post-test results. The identification and analysis of required documents revealed a transition from individual nazhirs to institutional nazhirs. The assistance also covered the preparation of audit willingness statements and the facilitation of nazhir replacement meetings, along with the creation of official replacement minutes. Overall, this legal assistance proved effective in ensuring the completeness of documents and compliance with the nazhir replacement process, contributing to better and more regulated waqf management.